2022
DOI: 10.1540/jsmr.58.78
|View full text |Cite
|
Sign up to set email alerts
|

Hangekobokuto, a traditional Japanese herbal medicine, ameliorates postoperative ileus through its anti-inflammatory action

Abstract: Background/Aims: Gastroprokinetic agents are used for patients with postoperative ileus (POI), and the Japanese traditional herbal medicine daikenchuto (DKT) is one such agent used in the clinical setting.POI is caused by inflammation. DKT and rikkunshito have anti-inflammatory abilities in addition to their gastroprokinetic effects. The efficacy of Kampo formulations, including hangekobokuto (HKT), in patients with POI has been reported recently. Several authors have described the efficacy of honokiol, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Characterisation of the IR genes restored by HKT (Figure 5C) showed that inflammation-related genes were the major restored IR genes (24 genes; 37.5%), with 7 mitochondria-related and 7 cilia-related genes each accounting for 10.9%. The anti-inflammatory effect shown here is consistent with the reported efficacy of many Japanese herbal medicines (31), including HKT (30). Interestingly, while HKT has been reported to have anti-inflammatory effects by reducing inducible nitric oxide synthase (iNOS), the IR of NOSIP (48), which has been reported as a modulator of NO, was consistently restored in the present study.…”
Section: Recovery Of Ir Genes By Administration Of Hktsupporting
confidence: 90%
See 2 more Smart Citations
“…Characterisation of the IR genes restored by HKT (Figure 5C) showed that inflammation-related genes were the major restored IR genes (24 genes; 37.5%), with 7 mitochondria-related and 7 cilia-related genes each accounting for 10.9%. The anti-inflammatory effect shown here is consistent with the reported efficacy of many Japanese herbal medicines (31), including HKT (30). Interestingly, while HKT has been reported to have anti-inflammatory effects by reducing inducible nitric oxide synthase (iNOS), the IR of NOSIP (48), which has been reported as a modulator of NO, was consistently restored in the present study.…”
Section: Recovery Of Ir Genes By Administration Of Hktsupporting
confidence: 90%
“…Japanese herbal medicines originated in ancient China and are widely used in Japan for a variety of conditions (31, 32). HKT (30) is one of the formulations and is taken for symptoms of mental anxiety, stagnant gas in the stomach and usually poor digestive function. In this study, HKT was used as a decoction in the following proportions, based on the formula of the Kitasato University Oriental Medicine Research Centre: Hange (Pinelliae Tuber) 6.0 g; Bukuryo (Hoelen) 5.0 g; Koboku (Magnoliae Cortex) 3.0 g, Shisoyo (Perillae Herba) 2.0 g; Syokyo (Zingiberis Rhizoma) 0.5 g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…induction. In contrast, the increased IL-1β and IL-6 expressions associated with iNOS induction were not restored by HKT, and no increase in NGF expression was seen [60].…”
Section: Effects On Gastrointestinal Motilitymentioning
confidence: 86%
“…In addition, it decreased the production of inducible NOS (iNOS) and increased the expression of nerve growth factor (NGF) and decreased nuclear factor‐κB (NFκB), respectively, which are associated with iNOS induction. In contrast, the increased IL‐1β and IL‐6 expressions associated with iNOS induction were not restored by HKT, and no increase in NGF expression was seen [60].…”
Section: Kampo Extract Formulation Administration Amount and Duration...mentioning
confidence: 99%